Shaping the field of lifelong education through three critical debates in the International Journal of Lifelong Education. Issue 6 (2nd November 2022) - Holford, John; Milana, Marcella; Webb, Susan; Waller, Richard; Hodge, Steven; Knight, Elizabeth
ABSTRACT: The editors approached the 40th anniversary of the International Journal of Lifelong Education as an opportunity to consider the field by exploring how a corpus of 1462 articles (the first 40 volumes of the journal) questioned and shaped the field. A subset of advisory board members and the editors gathered in 2021 in groups to analyse major topics. The records of the reading, analyses and discussions of these groups offer a unique snapshot of the field and the journal's place in it. In this paper, the editors draw three topics from that work which delineate fundamental debates of lifelong education and reveal how the journal's authors have contributed to them. The topics are: citizenship and its learning; learning in, through and for work; and widening participation and higher education. Comparing the works contributing to these topical areas indicates how the field is evolving. It becomes clear that research and theory in lifelong education should remain vigilant, critical and robust if the field is to continue as a site of hope for future citizens, workers and students, rather than appropriated as an object for measurement, calculation and deployment for relatively narrow, less-than-human interests.